2018
DOI: 10.1055/s-0038-1649481
|View full text |Cite
|
Sign up to set email alerts
|

Severe Maternal Morbidity and Hospital Cost among Hospitalized Deliveries in the United States

Abstract: The hospital cost with any SMM was 2.1 times higher than those without any SMM. Our findings highlight the need to identify interventions and guide research efforts to mitigate the rate of SMM and its economic burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…7,12 However, previous studies of SMM in the US have primarily focused on severe complications during the delivery hospitalization because of limitations in available data. 5,6,[13][14][15] A few exceptions are noted in studies by Callaghan et al, 6 Harvey et al, 16 and Girsen et al 17 Nonetheless, little is known about the rate and pattern of de novo postpartum SMM because these studies did not explicitly examine such cases. Similar to pregnancy-associated mortality, the distribution and characteristics of SMM that is first diagnosed during the delivery hospitalization may differ from those of SMM that first occurs after delivery discharge.…”
Section: Introductionmentioning
confidence: 99%
“…7,12 However, previous studies of SMM in the US have primarily focused on severe complications during the delivery hospitalization because of limitations in available data. 5,6,[13][14][15] A few exceptions are noted in studies by Callaghan et al, 6 Harvey et al, 16 and Girsen et al 17 Nonetheless, little is known about the rate and pattern of de novo postpartum SMM because these studies did not explicitly examine such cases. Similar to pregnancy-associated mortality, the distribution and characteristics of SMM that is first diagnosed during the delivery hospitalization may differ from those of SMM that first occurs after delivery discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Severe maternal morbidity (SMM), or unexpected life-threatening complications during delivery hospitalization, carries significant health and economic consequences. 1,2 Over the past few decades, the US SMM rate has steadily increased through at least 2014. 3,4 While the reasons for this rise are not fully known, the increasing prevalence of chronic conditions and other health risks among women prior to and during pregnancy (eg, hypertension, diabetes, and obesity) are likely contributors.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the NIS and NYC studies analyzed mixed populations of commercially insured and Medicaid patients (the former 50% Commercial and 44% Medicaid patients and the latter 38% Commercial and 58% Medicaid patients). 14 , 15 In addition, the earlier studies used an algorithm for identifying SMM based on ICD-9 codes, whereas the present study was based on ICD-10 codes. 14–16 …”
Section: Discussionmentioning
confidence: 98%
“…Two earlier studies reported delivery hospitalization costs associated with SMM, using, respectively, discharge data from the 2011 National Inpatient Sample (NIS) and a dataset of all delivery hospitalizations in New York City (NYC) from 2008 to 2012. 14 , 15 Direct comparison of these delivery cost estimates with estimates based on reimbursements in separate Commercial and Medicaid populations is difficult, given the different population structures and cost data sources. The earlier analyses estimated the costs expended by the hospital but excluded physician expenses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation